Further Development of an Integrated Web-Based Information System Supporting Tri Dharma at an Indonesian Aviation Academy - Hasyim Asari; Miko Andi Wardana; Putra Wicaksono; Nafana Aulia Rochida; Hendra Audarso (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2026)
Digital transformation requires higher education institutions to integrate academic, research, and community-service data into systems that are efficient, traceable, and easy to use. This study reports the further development of an integrated web-based information system at Akademi Penerbang Indonesia Banyuwangi to strengthen the management of Tri Dharma activities. The study applied a Research and Development design combining qualitative needs identification with quantitative post-development user evaluation. Initial needs were identified through observation and interviews with five lecturers and five education staff. The improved system integrated activity data, strengthened monitoring and reporting, and added research-budget management functions, including budget-component input, PDF export, financial approval, and revision notes. The developed system was subsequently evaluated by 28 respondents selected from a population of 30 users using a five-point Likert questionnaire consisting of 15 items. The overall mean score was 4.45, which falls within the 'strongly agree' category. The highest mean score was 4.57 for easier access to academic information and support for research management, while data security received the lowest mean of 4.25 but remained in the same category. The findings indicate that the continued development improves usability, data-management efficiency, and institutional coordination while highlighting security as a priority for further enhancement.